PERANCANGAN PENEMPATAN RECLOSER YANG OPTIMUM MENGGUNAKAN METODE QUANTUM GENETIC ALGORITHM DI PENYULANG PALAPA - I Gede Wiyoga Putra; I Gede Dyana Arjana; Widyadi Setiawan (Program Studi Teknik Elektro UNUD, 2020)
The need for electricity in Bali is increasing along with the growth of technology and developmentin Bali, so the quality of electricity distribution to customers must also be improved. This study took anexample from the 2018 case, Palapa Feeder used 2 reclosers which had an index value that did not meetthe standard of the reliability index value. When the Palapa Feeder only used LBS, SAIFI value was2.1055 and SAIDI was 7.2960, when the LBS was changed to recloser the SAIFI value was 1.203 andSAIDI was 4.091. When a recloser was added again the SAIFI value became 1.016 and SAIDI became3.4088. The use of 2 reclosers on a feeder is less effective, because if they are placed at a close distance,then there will be two devices work simultaneously when there is a disturbance so that the area which isnot affected by the disturbance will also experience a power outage. Therefore it is necessary to design arecloser placement point in order to obtain lower reliability index value in order to meet the PLN standard(SPLN) No. 68-2: 1986, World Class Company standards, World Class Service standards, and alsoobtained the optimum recloser location and more efficient.The design of recloser placement is carried out using the Quantum Genetic Algorithm method,which is an evolutionary algorithm based on the concept of quantum bits (qubits). The purpose of thismethod is to minimize the SAIDI and SAIFI value in order to obtain lower reliability index and meet thestandards in order to obtain an optimum recloser location. The results of the recloser placement designusing the QGA method show that the local optimum recloser location is in section 2 at point 56 with thehighest fitness value is 4.9715 and a SAIDI value is 1.8951 decreased by 44.4% and SAIFI value is 0.9978decreased by 1, 78%, and it is proven that the recloser placement design using the QGA method hassucceeded in obtaining local optimum with better SAIDI SAIFI index results and has met the PLN (SPLN)standard No. 68-2: 1986 with SAIDI 3,33 and SAIFI 1,2 and also meets World Class Company and WorldClass Service standards with SAIFI 3 (times/customer/year) and SAIDI 1,66 (hours/customer/year).